Are open educational resources (OER) and practices (OEP) effective in improving learning achievement? A meta-analysis and research synthesis - Tlili, Ahmed; Garzón, Juan; Salha, Soheil Hussein; Huang, Ronghuai; Xu, Lin; Burgos, Daniel; Denden, Mouna; Farrell, Orna; Farrow, Robert; Bozkurt, Aras; Amiel, Tel; McGreal, Rory; et al. (International Journal of Educational Technology in Higher Education, 2024)
While several studies have investigated the various effects of open educational resources (OER) and open educational practices (OEP), few have focused on its connection to learning achievement. The related scientific literature is divided about the effects of OER and OEP with regards to their contribution to learning achievement. To address this tension, a meta-analysis and research synthesis of 25 studies (N = 119,840 participants) was conducted to quantitatively investigate the effects of OER and OEP on students’ learning achievement. The analysis included course subject, level of education, intervention duration, sample size, geographical distribution, and research design as moderating variables of the obtained effects. The findings revealed that OER and OEP have a significant yet negligible (g = 0.07, p < 0.001) effect. Additionally, the analysis found that the obtained effect can be moderated by several variables, including course subject, level of education and geographical distribution. The study findings can help various stakeholders (e.g., educators, instructional designers or policy makers) in understanding what might hinder OER and OEP effect on learning achievement, hence accommodating better learning outcomes and more effective interventions.
Keywords: learning achievement; meta-analysis; meta-synthesis; open educational practices; open educational resources; Scopus; JCR